Majaz Mursal in the Qur'an Surah An-Nisa and Relevance to Women's Education - Hanifah Nurfitri; Zakiyah, Febri Nur; Sopian, Asep (Assuthur: Jurnal Pendidikan Bahasa Arab, 2024)
The Al-Qur’an is a guide to life for Muslims which contains many majaz and has educational values. One of the letters of the Qur'an that will be studied is the letter An-Nisa. This research aims to examine the mursal majaz contained in the An-Nisa letter and its relevance to aspects of women's education. The method used is qualitative with a heritage study approach. Research data was obtained from the verses of An-Nisa's letter using thematic - comparative - and semantic methods. The results of the research show that in An-Nisa's letter there are 29 pieces of data that are ordered as majaz mursal. This research shows that the majaz in the Koran, especially Surah An-Nisa, has great potential to be applied in women's education. By understanding these majaz, it is hoped that women can be more motivated to improve their self-quality and contribute positively in various areas of life.